2013
DOI: 10.1093/nar/gkt070
|View full text |Cite
|
Sign up to set email alerts
|

A systemic transcriptome analysis reveals the regulation of neural stem cell maintenance by an E2F1–miRNA feedback loop

Abstract: Stem cell fate decisions are controlled by a molecular network in which transcription factors and miRNAs are of key importance. To systemically investigate their impact on neural stem cell (NSC) maintenance and neuronal commitment, we performed a high-throughput mRNA and miRNA profiling and isolated functional interaction networks of involved mechanisms. Thereby, we identified an E2F1–miRNA feedback loop as important regulator of NSC fate decisions. Although E2F1 supports NSC proliferation and represses transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 55 publications
2
34
1
Order By: Relevance
“…Cluster 1 was defined by genes primarily associated with proliferation and neurogenesis, including genes involved in chromosome and DNA packing (for example, Mtfhfd1), replication (for example, Mybl2, Pcna) and cell cycle regulation (for example, Ccna2, Cdc73). This cluster was also characterized by the expression of transcription factor E2f1 and cyclin D1 (Ccnd1), with well established functions in the control of cell cycle [19][20][21]. Cluster 2 was defined by GO terms related to interneuron differentiation, cell morphogenesis and forebrain development, suggesting that this cluster contains interneuron precursors that have left the cell cycle and become postmitotic.…”
Section: Resultsmentioning
confidence: 99%
“…Cluster 1 was defined by genes primarily associated with proliferation and neurogenesis, including genes involved in chromosome and DNA packing (for example, Mtfhfd1), replication (for example, Mybl2, Pcna) and cell cycle regulation (for example, Ccna2, Cdc73). This cluster was also characterized by the expression of transcription factor E2f1 and cyclin D1 (Ccnd1), with well established functions in the control of cell cycle [19][20][21]. Cluster 2 was defined by GO terms related to interneuron differentiation, cell morphogenesis and forebrain development, suggesting that this cluster contains interneuron precursors that have left the cell cycle and become postmitotic.…”
Section: Resultsmentioning
confidence: 99%
“…In line with the promoter analysis, E2F1 expression and its target genes were found to be downregulated upon ENPP1 knockdown. Although a stem cell relevant role of E2F1 was so far not investigated in GSCs, E2F1 was shown to be of particular importance in the maintenance of neural stem cells 41 and human pluripotent stem cells 42 as well as in a transcriptional regulatory network governing the maintenance of embryonic stem cells. 43 Given the central role of E2F1 in the regulation of cell cycle progression, it is reasonable to assume that the observed reduced proliferation and accumulation of cells in G1 cell cycle phase in E-NPP1-deficient GSCs is mediated by a decreased transcriptional function of E2F1.…”
Section: Discussionmentioning
confidence: 99%
“…By performing a high-throughput mRNA and miRNA profiling, the researchers revealed that neuronal differentiation of NSCs induces drastic changes in the transcriptomic profile. These changes include the activation of numerous miRNAs [27]. QPCR results indicated that 3D culture environments contribute to maintain the self-renewal ability of NSCs.…”
Section: Figmentioning
confidence: 96%